Ipilimumab/Nivolumab-related Opsoclonus-Myoclonus-Ataxia Syndrome Variant in a Patient with Malignant Pleural Mesothelioma. Issue 9 (November 2018) - Maller, Bradley; Peguero, Edwin; Tanvetyanon, Tawee
Abstract : Introduction: Ipilimumab and nivolumab are immune-checkpoint inhibitors commonly used for melanoma. The combination is being investigated for its efficacy against several types of cancer, including malignant pleural mesothelioma. Although immune-related adverse events have been reported in patients receiving immune-checkpoint inhibitors, opsoclonus-myoclonus-ataxia syndrome has never been previously described. Case Presentation: We describe a 74-year-old male with malignant pleural mesothelioma who presented with opsoclonus and marked truncal ataxia ∼10 weeks following immunotherapy with ipilimumab and nivolumab. No myoclonus was present. Oligoclonal bands were detected in cerebrospinal fluid. Treatment with methylprednisolone and intravenous immunoglobulin along with clonazepam and valproic acid resulted in a rapid clinical improvement. A follow-up visit 2 months afterward showed a resolution of opsoclonus and he was able to walk with cane. Conclusions: A variant of opsoclonus-myoclonus-ataxia syndrome may occur following treatment with ipilimumab and nivolumab.